2019
DOI: 10.1055/a-0897-844
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Osteocalcin and C-Reactive Protein; A Relation of Bone with Inflammation: A Systematic Review and Meta-Analysis

Abstract: A meta-analysis was performed to summarize the evidence from observational studies regarding the association between serum osteocalcin (OC) and C-reactive protein (CRP). A systemic research of the literature databases including PubMed, SCOPUS, and Google Scholar was performed to identify the relevant studies up to March 2018. We used the random-effects model by the method of DerSimonian and Laird to calculate the overall effect size. Q-test and I 2-statistics were used to assess between-study heterogeneity. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 68 publications
0
2
1
Order By: Relevance
“…Given that the kidneys remove circulating OC, OC clearance probably decreases in people with impaired kidney function [28]. A meta-analysis reported a significant inverse association between the levels of serum OC and CRP in the adult population [29]. However, in our study, the serum log-CRP levels were positively correlated with the OC levels in patients with hypertension.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…Given that the kidneys remove circulating OC, OC clearance probably decreases in people with impaired kidney function [28]. A meta-analysis reported a significant inverse association between the levels of serum OC and CRP in the adult population [29]. However, in our study, the serum log-CRP levels were positively correlated with the OC levels in patients with hypertension.…”
Section: Discussioncontrasting
confidence: 64%
“…However, in our study, the serum log-CRP levels were positively correlated with the OC levels in patients with hypertension. Many factors may have affected the consistent and inconsistent findings on OC levels and CRP, including different methods for measuring OC, potential confounders that were not considered, and only observational studies used in the meta-analysis [29]. It will take more investigation to completely comprehend the mechanisms underlying the association between OC and CRP.…”
Section: Discussionmentioning
confidence: 99%
“…Ocn -/- mice presented increased total body fat and hepatic and AT inflammation, along with decreased insulin sensitivity and total energy expenditure [ 201 ]. Meta-analyses of clinical studies showed inverse correlations between OCN levels and BMI [ 202 ], insulin resistance [ 203 ], the inflammatory marker CRP [ 204 ], body fat mass [ 205 ], and specifically, visceral fat mass, determined with radiologic imaging studies [ 206 , 207 , 208 ]. Importantly, OCN was independently associated with visceral fat area [ 206 ], implying an involvement in the regulation of VAT.…”
Section: The Role Of Osteokines In Metabolic Pathways During Exercmentioning
confidence: 99%